Clients’ experiences and satisfaction with produce prescription programs in California: a qualitative evaluation to inform person-centered and respectful program models - Rhodes, Elizabeth C.; Pérez-Escamilla, Rafael; Okoli, Ngozi; Hromi-Fiedler, Amber; Foster, Jaime; McAndrew, John; Duran-Becerra, Beatriz; Duffany, Kathleen O’Connor (Frontiers in Public Health, 2024)
Background Produce prescription programs have strong potential to improve food security, fruit and vegetable consumption, and health across the life course. Understanding clients’ experiences and satisfaction with produce prescription programs is critical for evaluating the person-centeredness and quality of these programs. The objectives of this study were to (1) describe client experiences and satisfaction with produce prescription programs, with an emphasis on the extent to which they felt they were treated with respect and dignity, and (2) identify recommendations for improving client experiences. Methods We conducted four focus group discussions with clients of produce prescription programs in two Federally Qualified Health Centers in California. We used a modified framework analysis approach and organized participants’ experiences with programs into themes. Results Three themes captured participants’ program experiences. First, respectful produce prescription programming encompassed interactions with individuals delivering the programs that felt respectful (e.g., program staff showing they cared about participants’ health and offering timely assistance with financial incentives) and disrespectful (e.g., not receiving prompt responses to questions about incentives), as well as aspects of program design perceived to be respectful (e.g., provision of gift cards as financial incentives, which offered privacy when purchasing produce). Second, having autonomy to use gift cards to choose their preferred fresh fruits and vegetables was viewed as a positive experience, though participants desired greater autonomy to shop at stores other than the program designated stores. Third, participants frequently discussed program usability, with some reporting that joining the programs and using the cards was easy, and others describing difficulties activating cards and using them at stores due to cashiers’ lack of awareness of the programs. Overall, participants were highly satisfied with the programs. To improve client experiences, they recommended increasing privacy (e.g., by educating cashiers on the programs so that clients do not need to explain in public what the card is for) and autonomy (e.g., allowing cards to be used at other chain or local stores). Discussion Our findings inform efforts to make produce prescription programs more person-centered and respectful, which in turn may increase program demand, engagement, and impact.